Healthy Beauty / Efina Hamdan and Siti Nasarah Ismail - Hamdan, Efina; Ismail, Siti Nasarah (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2021)
Good health is the greatest gift a person can have. Being called beautiful is the best feeling a woman can experience. Looking healthy by having both beautiful and healthy body is a blessing that women appreciate most. Taking good care of yourself; eating nourishing food, getting enough sleep and regularly exercising are proof that beauty ties to wellness. The essence of beauty is looking healthy and being comfortable in one’s own skin. It helps to build self-confidence and improve communication skills. Looking and feeling healthy is not cheap. Visits to the spa, salon and beauty parlour may harm your wallet but worry no more; there are a lot of beneficial home remedies you can do that is friendly to you and your wallet. The essential of home remedy is to be resourceful with items and products around you. Let’s begin with the easiest one that uses only two ingredients that are available in every household, which are sugar and honey. These two ingredients can help you treat chapped lips.